2014
DOI: 10.1590/s0100-736x2014000900008
|View full text |Cite
|
Sign up to set email alerts
|

Senecio madagascariensis Poir. (Asteraceae): uma nova causa de seneciose em bovinos no Sul do Rio Grande do Sul

Abstract: Pesq. Vet. Bras. 34(9):851-855, setembro 2014 851 RESUMO.-Descrevem-se dois surtos de intoxicação por Senecio madagascariensis Poir. diagnosticados em bovinos em outubro de 2013 na região sul do Rio Grande do Sul. A morbidade foi de 3,2% e de 6,1% respectivamente e a letalidade foi de 100%. Um terceiro caso da intoxicação ocorreu em uma propriedade na qual de 54 bovinos um morreu com sinais clínicos da intoxicação. Em todos os casos, os bovinos estavam em áreas altamente infestas por S. madagascariensis que se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
4
0
4
Order By: Relevance
“…Another factor involved could be the variation in the number of PAs present in these species when compared to S. vernonioides, which presented DPHA dose of 19,599μg/g, with S. conyzaefolius presenting 2,500μg/g and S. paulensis 157μg/g. Stigger et al (2014) observed macroscopic lesions in bovines naturally poisoned by S. madagascariensis with PA doses of 500μg/g, lower than that found in S. conyzaefolius. The appearance of these lesions could be related to the period and amount of plant consumed, because in that case, animals were food restricted.…”
Section: Discussionmentioning
confidence: 57%
“…Another factor involved could be the variation in the number of PAs present in these species when compared to S. vernonioides, which presented DPHA dose of 19,599μg/g, with S. conyzaefolius presenting 2,500μg/g and S. paulensis 157μg/g. Stigger et al (2014) observed macroscopic lesions in bovines naturally poisoned by S. madagascariensis with PA doses of 500μg/g, lower than that found in S. conyzaefolius. The appearance of these lesions could be related to the period and amount of plant consumed, because in that case, animals were food restricted.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to the many cases of S. brasiliensis, cases of natural intoxication caused by S. madagascariensis have been increasing in southern Brazil (Cruz et al 2010, Stigger et al 2014). This plant is native to Madagascar and South Africa.…”
Section: Morphological Characteristics Of Senecio Brasiliensis and Senecio Madagascariensismentioning
confidence: 99%
“…Depending on the source of information, there are between 90 (Cabrera 1957) and 128 (Motidome & Ferreira 1966) Senecio species in Brazil. Among them, nine have been reported as toxic to cattle: Senecio brasiliensis (Tokarnia & Döbereiner 1984, Méndez et al 1990, Driemeier et al 1991), S. cisplatinus, S. heterotrichius, S. selloi (Méndez et al 1990), S. oxyphyllus (Barros et al 1987a, S. madagascariensis (Cruz et al 2010, Stigger et al 2014, S. tweediei (Méndez & Riet-Correa 1993) and S. desiderabilis (Tokarnia et al 1990). The toxicity of latter was demonstrated only experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in cattle by Tokarnia & Döbereiner (1984) and later by Méndez et al (1987), Barros et al (1987), and Driemeier et al (1991). Other species of this gender were also described as poisoning for cattle: Senecio cisplatinus, S. heterotrichius, S. selloi, S. leptolobus (Barros et al 1987, Méndez et al 1987, S. tweediei , S. oxyphyllus (Karam et al 2004), and S. madagascariensis (Cruz et al 2010, Karam et al 2011, Stigger et al 2014.…”
Section: Introductionmentioning
confidence: 99%